The boys from little Mexico : a season chasing the American dream - Wilson, Steve, 1966- (Beacon Press, 2010)
Chronicles the 2005 Woodburn High soccer season, where an all-Hispanic team, led by their Irish-descended white coach, sought to finally defeat the wealthy suburban schools in their district.